PESAN MODERASI BERAGAMA FACEBOOK KH. AFIFUDDIN MUHAJIR DALAM MENGELOLA KERAGAMAN AGAMA PERSPEKTIF KEBEBASAN BERAGAMA DAN USHUL FIQH - Nahe'i Nahe'i; Moh Soleh Shofier (LP2M Universitas Ibrahimy, 2025)
This study examines the messages of religious moderation delivered by one of the scholars popular among millennials, KH. Afifuddin Muhajir, through his personal Facebook account. The purpose of this study is to uncover the strategy and message of KH. Afifuddin Muhajir. Using a literature review and descriptive-analytical methods, this paper attempts to explain how the message of religious moderation, as exemplified by KH Afifuddin Muhajir, was conveyed through the social media platform Facebook. After that, with the perspective of Freedom of Religion and Belief (KBB) and ushul fiqh, this paper also analyzes the message of religious moderation KH. Afifuddin Muhajir. The results of this study show that religious moderation messages on Facebook KH. Afifuddin Muhajir employs several strategies. Among them are forms of stylistic presentation that are informative, persuasive, and coercive, which include commands, prohibitions, and questions (rhetorical). Meanwhile, a religious moderation message on Facebook KH. Afifuddin Muhajir cannot be separated from the indicators of religious moderation, according to the Ministry of Religious Affairs, which include national commitment, tolerance, non-violence, and accommodation to local culture. It aligns with KBB theory, which incorporates indicators of forum internum and forum externum.